Perlindungan Hukum Merek Terkenal di Negara-Negara ASEAN - Sinaga, Valerie Selvie (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
The strength of a well-known trademark crosses the various trademark registration classes. Thiis article is intended to discusses the legal protection of well-known trademarks in the jurisdiction of all the Association of Southeast Asian Nations (ASEAN) member states. This research is normative juridical- research by conducting a literature study to obtain legal materials. In the first part, it will be explained the definition of a well-known trademark that has been known in the world. Next, it will be discussed the criteria for a trademark to be considered well-known internationally. The last section discussed about the legal protection of well-known trademarks at the international level and at the national level in the ASEAN member countries. There are 3 types of well-known trademarks protection found in ASEAN member countries. First, the well-known trademarks are distinguished to be registered or unregistered. Registered well-known trademarks will be protected in all classes of goods or services, while well-known trademarks that are not registered only receive protection in the same classes of goods or services like those well-known trademarks. Countries that apply this kind of protection are the Philippines, Cambodia, Malaysia, and Myanmar. Second, the protection of well-known trademark is only in the same class of goods or services, regardless of whether the trademark is registered or not in the country. This type of protection is in Indonesia. Third, protection of well-known trademarks in all classes of goods or services without distinguishing whether the well-known trademark is already registered or not in the country. This kind of protection is known in Brunei, Laos, Thailand and Vietnam. Kekuatan suatu merek terkenal melintasi berbagai kelas pendaftaran merek. Tulisan ini bertujuan untuk membahas mengenai perlindungan hukum atas merek terkenal pada yurisdiksi seluruh negara anggota the Association of Southeast Asian Nations (ASEAN). Penelitian ini merupakan penelitian yuridis normatif dengan melakukan studi pustaka untuk menemukan bahan hukun. Pada bagian pertama akan dijelaskan mengenai definisi merek terkenal yang selama ini dikenal di dunia. Selanjutnya akan dibahas mengenai kriteria keterkenalan suatu merek terkenal secara internasional. Pada bagian terakhir dibahas mengenai perlindungan merek terkenal di tingkat internasional dan pada tingkat nasional di negara anggota ASEAN. Dapat disimpulkan terdapat 3 jenis perlindungan merek terkenal yang terdapat di negara-negara anggota ASEAN. Yang pertama adalah, merek terkenal dibedakan menjadi terdaftar atau tidak terdaftar. Merek terkenal yang terdaftar akan mendapat perlindungan di semua kelas barang atau jasa, sedangkan merek terkenal yang tidak terdaftar hanya mendapat perlindungan di kelas barang atau jasa yang sejenis dengan merek terkenal tersebut. Negara yang menerapkan perlindungan semacam ini adalah Filipina, Kamboja, Malaysia dan Myanmar. Yang kedua, perlindungan atas merek terkenal hanya di kelas barang atau jasa yang sama, terlepas dari apakah merek terkenal tersebut sudah terdaftar atau tidak di negara tersebut. Perlindungan jenis ini terdapat di Indonesia. Yang ketiga, perlindungan atas merek terkenal di semua kelas barang atau jasa tanpa membedakan apakah merek terkenal tersebut sudah terdaftar atau tidak di negara tersebut. Perlindungan semacam ini dikenal di Brunei, Laos, Thailand dan Vietnam.